Narrativa de aventura no ensino fundamental I: letramento literário aliado ao podcast - Elizabete Alves Santana Depollo (2020)
This work has a propositional character, in compliance with Resolution nº 003 of June 2, 2020 of the Profletras Management Council, presents a proposal for a systematic didactic sequence, based on the reflection that aims to provide elementary school teachers I, precisely the fourth year, the instrumentalizations for the development of a methodology guided by practices for the development of literary literacy, in the light of Cosson’s theory (2018). We suggest performing mediated and shared reading activities through debates and contextualizations necessary to foster the development of reading skills, in order to lead the student to a satisfactory immersion in a literary work. We selected the adventure narrative as it is considered to be a potent attraction for the age group of the fourth year of elementary school and we intend to honor and value verbal production in the formation of autonomous readers allied to the podcast media. We offer suggestions for practical reading lessons, sometimes individual, sometimes shared, in the classroom, in the library, or in the school garden and at home, in which we intend to convince small readers that everywhere we can enjoy a good read. With this proposal of pedagogical intervention, we aim to improve the development of literary literacy from the adventure narrative, creating conditions to awaken the taste and pleasure of reading in children of the fourth fundamental year. We conceived that the shared and well-mediated reading by the teacher enables the development of certain reading strategies, allows the student to capture details of the story, interact, imagine places, scenarios and characters, propose solutions, make predictions, make various inferences to understand the meaning of certain words, participate as a reader / listener in the development of the proposed actions. With proper mediation in this reading / discovery process and participation in the construction of meanings for the work, we have the opportunity to win over both students and families in developing a taste for reading literary works. Technology will be present throughout the execution of this intervention proposal, aiming to provide students with the possibility of acquiring multi-tools based on familiarization and the conscious use of internet resources and social networks for the production of material and texts , in which the mediation of the teacher becomes, vehemently, essential, in the planned conduction of actions that will foster a conscious and responsible user of these technological resources.